ANALISIS STRATEGI PEMASARAN DALAM UPAYA MENINGKATKAN PENJUALAN PADA USAHA MAKARONI KRIUKZZ - Rizqi Putra Ramadhan; Ovin Liviana Bela; Hendra Dwi Prasetyo (LP2M Universitas Bina Bangsa, 2022)
The writing of this article was made with the aim of knowing what marketing strategies are used by Kriukzz business actors in increasing sales. In this study using a qualitative descriptive approach. The types and sources of data in writing this article are taken from primary data and secondary data. The analysis method used is descriptive analysis, where the marketing strategy refers to the concept of Marketing mix and uses SWOT analysis. Based on the analysis carried out in increasing the sales of this kriukzz macaroni using the 4P marketing mix and SWOT analysis (strengths, weaknesses, opportunities, threats). The results of this study can determine the implementation of the 4P marketing mix marketing strategy and SWOT method analysis in an effort to increase sales of Kriukzz products